Traceability Part For Meter A14C5 In PT Mecoindo Of The Measurement Of Quality Of Use - . Suratman; Wahyu Hadi Kristanto; Asep Suprianto; Muhamad Fatchan; Dendy Pramudito (International Conference on Engineering and Technology Development (ICETD), 2012)
With the expansion of global trade, computerization and communications, plain language descriptions of products and services need to be replaced by identification and product tracing systems that are usable in all trade and industry sectors worldwide. Product traceability is the process of maintaining records of all materials and parts from purchasing to finished goods where a unique number identify a part, batch, or a finished product.Traceability provides the ability to identify and track a product or a component to its point of origin. The point of origin may be a particular lot or batch, production line and time frame, field, or supplier. Product traceability is very important to reliability. If a particular lot of a critical component is found to be defective after being used in product that is already sold, traceability provides a means of identifying the units for recall. Some products (e.g. aircraft components, fresh produce, meat) require complete traceability. Here are some of the benefits and solutions provided with product identification and tracing: Procedures for identifying and tracing the product during all stages of production, delivery & installation; Requires knowing what parts comprise the product, their specification, their status, etc; Requires knowing the exact content of products that have been delivered to each customer so that the right customer service can be provided; Helps to satisfy âProcess Controlâ.In this paper we are going to accent on EAN UCC numbering system where EAN stands for European Article Numbering and UCC stands for Uniform Code Council. EAN/UCC numbers provide unique and unambiguous identification for worldwide recognition and can improve the efficiency and exchanging information between supply chain participants.Parts Traceability Information System used by PT. Mecoin do to record a part-part starting from the arrival until assembled into products used by each part will kWh meter. So that in a product can be traced GRS kWh meter that is used by each part. As for the concept of the approach taken is an object-oriented approach is to view the problem by using a model - a model that is organized (which combines the issues surrounding the concept of data structure and behavior of an entity). In this approach, the software organization is a collection of discrete objects that work together, communicate and interact to a certain target.